The handbook of the psychology of communication technology - Sundar, S. Shyam (Wiley Blackwell, 2015)
"The handbook of the psychology of communication technology offers an unparalleled source for seminal and cutting-edge research on the psychological aspects of communicating with and via emergent media technologies, with leading scholars providing insights that advance our knowledge on human-technology interactions" -- provided by Publisher.